The Effect of Employer Branding and Fair Compensation on Doctors and Nurses’ Retention in Kano State Tertiary Health Centers - TSINTOP USSAINI DANJUMA, (Research in Management of Technology and Business, 2024)
This study examines the critical role of employer branding and fair compensation in addressing the retention challenges faced by doctors and nurses in Kano State tertiary health centers. survey research design was employed with a total population of 2649 and a sample size of 435. Data were collected through the use of questionnaires. Convenience and stratified sampling strategies were used in this investigation. Validity and reliability were carried out to determine the fitness of the instrument. With the response rate of 92%. Data were analyzed using SPSS Version 25 with multiple regression techniques. Findings show a positive effect of employer branding and fair compensation on doctors and nurses’ retention in Kano State with the P value of.000, respectively.  The study recommends that enhanced employer branding strategies and fair compensation are crucial for improving retention rate among doctors and nurses in Kano State